2014
DOI: 10.1093/ckj/sfu130
|View full text |Cite
|
Sign up to set email alerts
|

Identification, investigation and management of patient-to-patient hepatitis B transmission within an inpatient renal ward in North West England

Abstract: BackgroundTransmission of hepatitis B virus (HBV) is rare within healthcare settings in developed countries. The aim of the article is to outline the process of identification and management of transmission of acute hepatitis B in a renal inpatient ward.MethodsThe case was identified through routine reporting to public health specialists, and epidemiological, virological and environmental assessment was undertaken to investigate the source of infection. An audit of HBV vaccination in patients with chronic kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In fact, outbreaks of viral hepatitis in the dialysis environment are not uncommon when infection control breaches occur 3 , 4 , 7 . Kliner et al 19 reported patient-to-patient transmission of HBV in a UK hemodialysis unit. According to these authors, the occurrence of this kind of event was attributed to non-compliance with infection control and prevention recommendations, which includes monitoring anti-HBs titers to indicate vaccination booster doses, when appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, outbreaks of viral hepatitis in the dialysis environment are not uncommon when infection control breaches occur 3 , 4 , 7 . Kliner et al 19 reported patient-to-patient transmission of HBV in a UK hemodialysis unit. According to these authors, the occurrence of this kind of event was attributed to non-compliance with infection control and prevention recommendations, which includes monitoring anti-HBs titers to indicate vaccination booster doses, when appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…143 Several recent outbreaks involving patient-to-patient HBV transmission have been recorded. [144][145][146] Outbreaks mostly occurred in renal ward/hemodialysis patients and were frequently related to lack of infection control measures. 145,146 Transmission from HCWs to patients has also been observed.…”
Section: Benefits and Risks In Healthcare Settingsmentioning
confidence: 99%
“…[144][145][146] Outbreaks mostly occurred in renal ward/hemodialysis patients and were frequently related to lack of infection control measures. 145,146 Transmission from HCWs to patients has also been observed. 147 The risk of HCWs acquiring HBV infection is related to the extent of percutaneous or mucosal exposure to blood and other bodily fluids.…”
Section: Benefits and Risks In Healthcare Settingsmentioning
confidence: 99%
“…In this issue, Kliner et al [ 3 ] report a case of hepatitis B virus contagion in an inpatient renal ward. Hepatitis B has been considered a major risk among haemodialysis patients and healthcare workers since the early times of the technique.…”
mentioning
confidence: 99%
“…The published case illustrates the need for a full epidemiological work-up in the case a recent hepatitis B infection is diagnosed. Thus, careful research following a new case of hepatitis B virus infection uncovered many failures, including poor vaccination status of patients and many violations of universal infection control measures, such as poor hand hygiene and visible contamination of blood glucose testing equipment [ 3 ]. It was concluded that patient-to-patient transmission was likely to have occurred on the renal ward due to multiple failures in infection control.…”
mentioning
confidence: 99%